Determination of risk factors for night eating syndrome among public university students in Malaysia - Gan, Wan Ying; Chin, Pei Qi; Law, Leh Shii (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Night eating syndrome (NES) has been progressively drawing attention and becoming a global concern due to its clinical implications. However, the study related to NES was found to be scarce in Malaysia. As such, this study aimed to determine the risk factors of NES among Malaysian public university students. Methods: This cross-sectional study involved 270 participants (mean age: 20.9±1.4 years), who were selected randomly from three different course disciplines at a public university in Selangor, Malaysia. The data were collected using a self-administered questionnaire on socio-demographic background, NES, depression, anxiety, stress, sleep quality, and disordered eating. Weight, height, and waist circumference of the participants were measured. Results: Results showed that 12.2% of the participants were engaged in NES. Binary logistic regression identified four significant risk factors of NES namely, being a male (AOR = 3.050, 95% CI = 1.129 – 8.238), persuading in a technical-stream course (AOR = 6.010, 95% CI = 2.057 – 17.555), being a stressful student (AOR = 3.580, 95% CI = 1.149 – 11.151), and having poor sleep quality (AOR = 4.664, 95% CI = 1.431 – 15.209). Conclusion: Early screening process should be conducted from time to time in which university students with potentially NES are able to receive necessary behavioural and cognitive therapy in order to recover.